Toward the Design of a Novel Wearable System for Field Research in Ecology - Silva, Mateus; Delabrida, Saul; Ribeiro, Servio; Oliveira, Ricardo R. (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2018)
The measurements of biotic and abiotic parameters in natural conditions are essential for ecologists. Wearable devices are changing the way how scientists can measure their study subject in extreme conditions. In this work, a new model of wearable device is presented to be used during the tree climbing performed by ecologists. The device architecture is designed to expand the perception of the researcher, using sensors as LIDAR and IMU units to present further information during research.